Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. MPM Finance - Abdul Rahman (Cakrawala Akuntansi & Manajemen, 2023)
This ponder points to decide and analyze the impact of the work environment and work teach mostly and at the same time on worker execution at PT. MPM Fund. The approach utilized in this investigate is quantitative investigate and the procedure utilized in this investigate is affiliated methodology. The investigate strategy that will be utilized may be a expressive examination strategy utilizing relapse examination, which is to discover out how much commitment / impact the work environment and teach have on worker execution at PT. MPM Back. In this think about, information handling was carried out utilizing SPSS ver. 24.00. The populace in this ponder is all workers of PT. MPM Back which has 300 individuals. The test utilized based on the slovin equation was 75 representatives at PT. MPM Fund. Based on investigation and discussion, it appears that the work environment encompasses a noteworthy positive impact on representative execution at PT. MPM Back, it can be seen that a critical esteem of 0.000 < 0.05 the primary